The emergence of scholarly literature on physical/social distancing related to Coronavirus: A bibliometric analysis - Nadeem Siddique; Shakil Ahmad; Asif Altaf; Khalid Mahmood; Abid Iqbal; Muhammad Ajmal Khan (SAGE Publishing, 2021)
Introduction: The world is witnessing new public health crises due to the emergence of the novel coronavirus. This study aims to present a bibliometric analysis of research on coronavirus-related physical/social distancing. Design and Methods: In this study, a bibliometric analysis was applied to see the research productivity and its impact on coronavirus-related physical/social distancing. For this purpose, Scopus was used to retrieve the data for the analysis. A total of 2900 records was downloaded from the database for analysis. Results: The findings revealed that the top four authors published their research in the year 2020. The study ranked the British Medical Journal (BMJ) at the top position on publishing the research on the topic. Similarly, the USA took the lead in all countries in producing research on the topic. The researchers preferred the document type 'Article' for sharing their research, and a single authorship pattern was dominated on all other patterns. Conclusions: Plenty of bibliometric studies are available on coronavirus, but not a single study is found on coronavirus-related physical/social distancing. This study will be valuable in identifying different bibliometric dimensions on the topic.